2003
DOI: 10.1074/jbc.m209337200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Residues Important for Ligand Binding of Thromboxane A2 Receptor in the Second Extracellular Loop Using the NMR Experiment-guided Mutagenesis Approach

Abstract: The second extracellular loop (eLP2) of the thromboxane A 2 receptor (TP) had been proposed to be involved in ligand binding. Through two-dimensional 1 H NMR experiments, the overall three-dimensional structure of a constrained synthetic peptide mimicking the eLP2 had been determined by our group (Ruan, K.-H., So, S.-P., Wu, J., Li, D., Huang, A., and Kung, J. (2001 Thromboxane A 2 (TXA 2 ) 1 is a potent platelet aggregatory and vasoconstrictive mediator (2). The function of TXA 2 is mediated by specific cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 25 publications
2
55
0
Order By: Relevance
“…Based on the TM domain model of the human TP receptor that was previously created by homology modeling using the X-ray structure of bovine rhodopsin as a template [29][30][31][32], the distance between the iLP2 termini, connected to the third and fourth TM domains is about 12.9 Å and the distance between the iLP3 termini connected to the fifth and sixth TM domains is about 12.4 Å ( Figure 1A). Two peptides corresponding to the TP iLP2 and TP iLP3 regions ( Figure 1B), which contained additional homocysteine residues at the N-and C-termini, were synthesized and constrained to a similar distance at the termini by a disulfide bond formation using a the fluorenyl-methoxy-carbonyl-polyamide solid phase method ( Figure 1C) [27,[29][30][31][32][33][34][35][36]. After synthesis, the peptides were purified to homogeneity by reverse phase HPLC using a C4 column, and the correct molecular weights were confirmed by mass spectrometry analysis [37].…”
Section: Design and Synthesis Of The Constrained Peptides Mimicking Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the TM domain model of the human TP receptor that was previously created by homology modeling using the X-ray structure of bovine rhodopsin as a template [29][30][31][32], the distance between the iLP2 termini, connected to the third and fourth TM domains is about 12.9 Å and the distance between the iLP3 termini connected to the fifth and sixth TM domains is about 12.4 Å ( Figure 1A). Two peptides corresponding to the TP iLP2 and TP iLP3 regions ( Figure 1B), which contained additional homocysteine residues at the N-and C-termini, were synthesized and constrained to a similar distance at the termini by a disulfide bond formation using a the fluorenyl-methoxy-carbonyl-polyamide solid phase method ( Figure 1C) [27,[29][30][31][32][33][34][35][36]. After synthesis, the peptides were purified to homogeneity by reverse phase HPLC using a C4 column, and the correct molecular weights were confirmed by mass spectrometry analysis [37].…”
Section: Design and Synthesis Of The Constrained Peptides Mimicking Tmentioning
confidence: 99%
“…1H 2D TOCSY, NOESY and DQF-COSY spectra were used to measure the constrained peptides. 1H NMR assignments were accomplished using the standard sequential assignment technique described [26,27,[29][30][31][32][33][34][35][36]. The assignment procedures involved in the identification of spin systems using the TOCSY spectra, and the sequential assignments using NOESY spectra were completed by manual assignment.…”
Section: Nmr Experiments and Resonance Assignmentsmentioning
confidence: 99%
“…The solution NMR structures of the TP extra- [29] and intra- [30] cellular loop segments were used to link the TM segments together to form a 3D TP model by using the Insight II protein modeling software. The PGH 2 mimics were docked into the ligand pocket that was previously predicted by NMR spectroscopic and mutagenesis studies [29,31], and by taking into account the ligand pocket in the β2 adrenergic receptor [32][33]. The docking study was performed by a 3D-Quantitative Structure Activity [34] using SYBYL Surflex-Dock software (Tripos, St. Louis, MO).…”
Section: Docking Of Pgh 2 Mimics Into the Putative Ligand-binding Sitmentioning
confidence: 99%
“…The TP extracellular loop structure was constructed by linking the NMR structures of the three loops to the corresponding TM domains and then optimized by energy minimization as described [29]. The TM ligand-binding site of the TP was localized by using previous mutagenesis information [31], which includes the interaction of the TP extracellular loop with its ligand, and the ligand pocket in the crystal structure of the β2 adrenergic receptor [32][33]. The NMR structure of the TP-bound U46619 conformation ( Figure 6B, rectangle shape) could fit into the putative ligand pocket very well ( Figure 7A).…”
Section: Docking Of the Tp-bound U46619 With The Ligand-binding Pockementioning
confidence: 99%
“…Recently, through a combination of the NMR spectroscopy technique, site-directed mutagenesis, peptide mimicking, and molecular modeling (21)(22)(23)(24)(25)(26) we have revealed the ligand-recognition site in the extracellular domains and identified that the second extracellular loop (22,25,26) plays a critical role in forming the ligand-recognition pocket (22,(24)(25)(26). However, it remains critical to understand the detailed molecular mechanisms for the ligand recognition, binding, and signaling activation of the native receptor.…”
Section: Introductionmentioning
confidence: 99%